Establishing milestones in urology training: A survey of the Canadian - Nayan, Madhur; Houle, Anne-Marie; McDougall, Elspeth; Fried, Gerald M.; Andonian, Sero (Canadian Urological Association Journal, 2013)
Background: At the current time, technical skills are not directly evaluated by the Royal College of Physicians and Surgeons of Canada (RCPSC) as part of the certification process in urology. Rather, the RCPSC relies on the evaluation of Program Directors to ensure that trainees have acquired the necessary surgical skills. Methods: An electronic survey was sent out to the members of the Canadian Academy of Urological Surgeons (CAUS), including the 13 Canadian urology program directors, to assess the teaching and evaluation of technical skills of urology trainees. Results: The response rate was 37% (33/89), including 8 of the 13 (62%) Program Directors from across Canada. For the teaching of technical skills, most programs had access to live animal laboratories (69%), dedicated teaching time in simulation (59%) and physical training models (59%). Most relied on voluntary faculty. There was a wide variety of structured evaluations for technical skills used across programs, while 36% of respondents did not use structured evaluations. For trainees with deficiencies in technical skills, 67% of programs offered extra operative time with designated faculty, 26% offered additional simulation focused on the deficiency and 19% offered faculty tutorial sessions. Conclusion: Among Canadian urology residency programs, there is considerable variability in the assessment of technical skills of trainees. Standardized objective assessment tools would help ensure that all trainees have acquired adequate surgical proficiency to operate independently.